ENVIRONMENTAL CONDITIONS IN ZHALAL-ABAD (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article reflects some environmental problems of the environment and ways to solve them, as well as the rational use of natural resources.
Keywords: nature, environmental problems, natural resources, environment, waste, thrift